ADMINISTRATIVE SYSTEM IN PURCHASING GOODS COMPANY KODECO ENERGY CO., LTD - Nur Achroni; Aqwqm Rosadi Kardian. Skom. MM (Jurnal Sistem Informasi, 2002)
Scientific writing is to explain about the processing of data concerning the purchaseof goods on the company's administration Kodeco energy co., Ltd.For data processing, purchasing administrative process, the author tries to make anapplication programming for energy companies co., Ltd where the author works thatare still done manually. This becomes a problem and the authors try to change it byway of analyzing problems, designing an application programming about the processof purchasing goods computerized administration, made an application in order tosimplify administrative tasks in the Vendor and the purchase of goods to reduceerrors that occur, than if carried out manual.Administrative system design begins with the purchase of goods and ending with theresearch field of scientific writing. Desired system design will be created using theDFD, Context Diagram, Diagram Zero, ERD, Normalization, and also useprogramming language Delphi.